366 Effect of Native Rumen Bacteria Supplementation in Methane Emissions, Growth Performance, and Carcass Characteristics of Feedlot Cattle. (21st September 2022) - Pittaluga, Alejandro; Yang, Fan; Embree, Jordan; Gilmore, Sean; Embree, Mallory; Relling, Alejandro E
Abstract: To evaluate the effect of supplementing feedlot cattle with native rumen bacteria (NRB; Prevotella albensis, Succinivibrio dextrinosolvens, and Chordicoccus furentiruminis) in growth performance, carcass characteristics and gas emissions, Angus × SimAngus-crossbred (body weight (BW) 353 ± 64 kg) steers (n = 32) and heifers (n = 48) were used in randomized complete block design. Cattle stratified by BW were randomly assigned to 4 pens (2/treatment) and fed a corn silage-based diet for 49 d (backgrounding) followed by a ground corn-based diet for 84 d (finishing). When reaching desired finished BW, cattle were harvested. Diets were offered ad libitum and with (WNB) or without (CON) the inclusion of NRB feed supplement. Measurements of CH4 emissions were taken using the GreenFeed system (n = 12/ treatment). All data were analyzed as a mixed procedure (Table 1). There was a treatment (P ≤ 0.05) effect for CH4 emissions yield [g/kg dry matter intake (DMI)] and intensity [g/kg average daily gain (ADG)] during the growing period. Including NRB in the diet during growing, decreased CH4 emissions yield and intensity by 13.5% and 29%, respectively. During the first 84-d period on the finishing diet (d133), feeding NRB increased (P = 0.02) the ADG and tended to increase (P = 0.10) DMI. At d133, cattle fed NRB tended (P = 0.06) to be heavier than cattle in the CON treatment. Days on feed (DOF) was 9 days longer for CON animals than those of WNB animals (P = 0.04). No other differences (P ≥ 0.25) were detected throughout the experimental period and no differences (P ≥ 0.11) were observed in carcass characteristics. Results from this study indicate that feeding NRB decreased methane yield and intensity in the backgrounding period, improved finishing performance of beef cattle, and decreased DOF